Optical Fiber Sensing of Salinity and Liquid Level - Yang, H.Z.; Qiao, X.G.; Lim, K.S.; Harun, Sulaiman Wadi; Chong, W.Y.; Islam, Md. Rajibul; Ahmad, Harith (Institute of Electrical and Electronics Engineers (IEEE), 2014)
This letter reports a fiber optic sensing technology for the detection of salinity and liquid level of a given solution. The operation principle is based on the displacement measurement in a large measuring range by generating a variety of outputs for various sensing objectives. The proposed sensor is investigated analytically and experimentally. The achieved salinity sensitivity is 8.589/%, in addition, the proposed sensor exhibits an excellent liquid level sensitivity of 0.4421/mm in the experiment.